Isolation of Neisseria gonorrhoeae Mutants That Show Enhanced Trafficking across Polarized T84 Epithelial Monolayers - Hopper, Sylvia (American Society for Microbiology, 2000)
Initiation of a gonococcal infection involves attachment of Neisseria gonorrhoeae to the plasma membrane of an epithelial cell in the mucosal epithelium and its internalization, transepithelial trafficking, and exocytosis from the basal membrane. Piliation and expression of certain Opa proteins and the immunoglobulin A1 protease influence the transcytosis process. We are interested in identifying other genetic determinants of N. gonorrhoeae that play a role in transcellular trafficking. Using polarized T84 monolayers as a model epithelial barrier, we have assayed an N. gonorrhoeae FA1090 minitransposon (mTn) mutant bank for isolates that traverse the monolayer more quickly than the isogenic wild-type (WT) strain. From an initial screen, we isolated four mutants, defining three genetic loci, that traverse monolayers significantly more quickly than their WT parent strain. These mutants adhere to and invade cells normally and do not affect the integrity of the monolayer barrier. Backcrosses of the mutations into the WT FA1090 strain yielded mutants with a similar fast-trafficking phenotype. In two mutants, the mTns had inserted 370 bp apart into the same locus, which we have named fit, for fast intracellular trafficker. Backcrosses of one of these mutants into the MS11A genetic background also yielded a fast-trafficking mutant. The fit locus contains two overlapping open reading frames, fitA and fitB, whose deduced amino acid sequences have predicted molecular weights of 8.6 and 15.3, respectively. Neither protein contains a signal sequence. FitA has a potential helix-turn-helix motif, while the deduced sequence of FitB offers no clues to its function. fitA or fitB homologues are present in the genomes of Pseudomonas syringae and Rhizobium meliloti, but not Neisseria meningitidis. Replication of the MS11A fitA mutant in A431 and T84 cells is significantly accelerated compared to that of the isogenic WT strain. In contrast, growth of this mutant in liquid media is normal. Taken together, these results strongly suggest that traversal of N. gonorrhoeae across an epithelial barrier is linked to intracellular bacterial growth.